Everyday life of Frianovo silk weaving factory workers in XVIII — first quarter of the XIX century - O. GOTOVTSOVA (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Based upon a wide range of archive records, the article covers issues relating to particular aspects of life and living standards of silk weaving factory workers’ families in a village of Fryanovo of Moskovski county in XVIII — fi rst quarter of XIX centuries.Workers’ daily life was signifi cantly infl uenced by living conditions. It is via this article that we analyze dimensions and types of living premises provided to workers by the factory owners, as well as its improvements. The Fryanovo factory offi ce records that remain intact allow consideration of issues relating to food for workers, including sources for providing Fryanovo inhabitants with bread and other food products, the composition and the average amount thereof.One chapter of the article is specifi cally devoted to workers’ worship service attendance, as well as diff erences in religion belief of Fryanovo inhabitants. In addition to the orthodox Christian majority of its population, there were also Catholics and Old Believers among its inhabitants.The issues directly relating to working at the silk weaving factory include work schedule and rules, average age of workers, wage payment methods, as well as workers motivation by the silk weaving factory owner. Considered are the issues relating to employment of children and women at the silk weaving factory. An important part of the research relates to living conditions of non-working population groups: young children, retired and handicaps who were given some money or bread, on monthly bases, by silk weaving factory owners.Medical services for the silk weaving factory workers, personal taxation and other fees, participation by factory workers, in recruitments, penalties and fi nes system as implemented by the silk weaving factory in Fryanovo are also within the spectrum of questions that are discussed within the article.The fi nal chapter of the research points out the village inner life issues, such as alcohol abuse among workers, crimes they committed, as well as workers’ interrelations with other neighbor villages inhabitants.In general, the matters considered allow improving understanding the life of workers and their families by large possession enterprises of Russia in XVIII — fi rst quarter of XIX centuries